The Use of Audiobooks in Developing Seventh-Grade Students' Reading Skills (A Case Study for EFL Students) - Hery Nuraini; Yeni Daniarti; Rohmat Taufiq (Lingua Cultura, 2020)
The research was conducted to develop students’ reading skills by using an English story with Audiobooks. It seemed that the teachers could overcome if they were proficient in utilizing the internet and computer applications in the students’ learning process because the students enjoyed the gedgets. In a sense, teachers should integrate supportive technology, problem-based approaches, and higher-order thinking skills. Based on these problems, the researcher was interested in developing students’ reading skills by using Audiobooks apps. Moreover, the research investigated that students could significantly develop their reading skills by reading English stories with Audiobooks apps. It aimed to investigate the students’ reading skills could significantly be developing by reading English stories with the Audiobooks app. The research applied a case study as the qualitative research method. The participants were three students from seventh-grade students. The researchers collected and analyzed the data from observations, tests, and interviews. Based on the finding and discussion, it can be concluded that the participants have achieved and exceeded in Standard Minimum Score (KKM). Besides, the students are enthusiastic and comfortable reading English stories with Audiobooks application in the learning process.